Intra-familial stigmatization: An adverse outcome of a family-based health education intervention to reduce childhood obesity. Issue 3 (3rd April 2018) - Hoeeg, Didde; Grabowski, Dan; Christensen, Ulla
Abstract : Purpose: To treat childhood obesity, health education interventions are often aimed at the whole family. However, such interventions seem to have a relatively limited effect on weight loss. The purpose of this paper is to examine how families enrolled in a family-based health education intervention manage the intervention in their daily lives and to understand how and why intra-familial conflicts may occur. Design/methodology/approach: Data consist of 10 in-depth semi-structured family interviews with 25 family members (10 children, 15 parents), who were enrolled in a family-based health education intervention for families with an obese child. Findings: Actively involving all family members in the intervention proved difficult in many families. Often, the children experienced inconsistent family support, which led to intra-familial conflicts. When parents were unsuccessful in changing unhealthy habits, the responsibility for healthy living was often passed on to the obese child. Thus, several families managed the intervention by making specific rules that only the obese child was required to adhere to. This resulted in several children feeling stigmatized in their own family. Practical implications: Professionals working with family-based health education interventions should understand that, in order to minimize the risk of intra-familial conflicts and stigmatization of the obese child, all family members must be equally committed to the lifestyle intervention. Originality/value: The study contributes to the existing literature by adding specific knowledge about how and why conflicts occur in these families and what the consequences of these conflicts are.